Prehistoric stone monuments - Martin, Ana.; Unesco (Chicago : Childrens Press, 1993)
Explores the origins and significance of the great stone monuments dating from the Neolithic Age which are found throughout Western Europe.
'UNESCO.'
Includes index.
Keywords: Megalithic monuments -- Europe -- Juvenile literature; Megalithic monuments -- Europe; Europe -- Antiquities -- Juvenile literature; Europe -- Antiquities